Mechanistic insights to the effective pathways of global and local climate change in a Baltic Sea seaweed - epiphyte - mesograzer system - Werner, Franziska Julie (2015)
Anthropogenic greenhouse gas emissions have been driving global climate change and they will continue to do so over the course of the 21st century. Most of the marine biosphere and especially coastal marine systems have suffered from high anthropogenic pressure per se and it is possible that the novel burden of very rapidly proceeding global climate change triggers shifts to alternative regimes and functioning in marine ecosystems. In the light of this background, my dissertation aims to contribute to the mechanistic understanding of global and local climate change effects on a common coastal marine seaweed (Fucus vesiculosus, Phaeophyceae) system of the Baltic Sea. The results of my experimental studies provide important mechanistic clues about the underlying direct and indirect effective pathways of environmental change in the studied seaweed system. To the best of my knowledge, it is one of the first studies which assess the seasonal variability of the same environmental factors on the same marine system over the course of one year. The detected context-dependency of global climate change effects within one ecosystem clearly shows that our understanding of the basic underlying ecosystem processes and patterns forms a prerequisite for testing, predicting and managing future ecological change in marine systems. Given that grazing forms a crucial ecological force in many coastal vegetated systems, the identified underlying mechanisms of change (top-down and bottom-up control) may allow reference to other similarly structured coastal systems. Importantly my findings point out, that ecological impacts of global climate change may be underestimated if local perturbation is disregarded and, thus, underline the chance and responsibility of local ecosystem management. Anthropogene Treibhausgasemissionen haben zu globalen Klimaveränderungen auf der Erde geführt und werden den Klimawandel im Verlauf des 21. Jahrhunderts vorantreiben. Da insbesondere küstennahe marine Ökosysteme bereits stark durch menschliche ...